THE THE EFFECT OF BOOKLET MEDIA ON IMPROVING STUDENTS KNOWLEDGE AND ATTITUDES TOWARD SEXUAL HARASSMENT - Rosita Rosita; Neng Yulia Ernawati; Sri Hennyati; Dyah Triwidiyantari; Lina Herlina (Program Studi Ners UNIVERSITAS SARI MUTIARA INDONESIA, 2026)
Background: Sexual harassment against women is a form of gender-based violence with serious impacts on mental, physical, and financial health, as well as on victims' daily activities. Its effects include anxiety disorders, depression, sleep disturbances, and sexual dysfunction. In 2023, there were 2,078 reported cases of sexual violence, and by January 2025, 2,681 cases were reported in higher education institutions. Purpose: This study aims to determine the effect of booklet media on adolescents' knowledge and attitudes regarding sexual harassment at SMP Pasundan I Banjaran. Methods: A pre-experimental design with a one-group pretest-posttest approach was used, involving 146 female students selected through simple random sampling. Primary data were analyzed using the Wilcoxon Signed Rank Test due to the non-normal data distribution. Results: The results showed a significant increase in knowledge (Z = -10.492; p < 0.05) and attitudes (Z = -10.311; p < 0.05) after the booklet intervention. Conclusion: Booklet media appeared effective in improving adolescents' knowledge and attitudes and may be suitable as an educational intervention to help prevent sexual harassment.